PEMANFAATAN KOMIK DIGITAL SEBAGAI SARANA BISNIS DIGITAL PADA MEDIA SOSIAL INSTAGRAM - Gede Lingga Ananta Kusuma Putra; Anak Agung Ngurah Bagus Kesuma Yudha (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2021)
Comics are increasingly being used as a means of doing business in today's era. Many companies, business entities and individuals do business through online media. The use of comics as a promotional medium in this digital era, of course, must pay attention to the advantages of using comics as a means of digital business. This study was conducted to determine the use of digital comics as a means of digital business on Instagram social media. The qualitative research method is carried out in an inductive way, namely examining the characteristics of each part in Digital Comics that is used as a Digital Business. The use of digital comics as a means of digital business is also a good choice, because by using digital comics the content will become more interesting because in the digital comics, illustrations and text balloons can be applied. Not only as an added attraction, but illustrations and text balloons can also be used as a means of delivering information in digital business activities.